FEMINISM STUDY THE MYTH BEAUTY OF FEMALE CHARACTERS IN THE NOVEL INDUK GAJAH BY IRA GITA SEMBIRING AS TEACHING MATERIAL FOR NOVEL TEXTS AT THE HIGH SCHOOL LEVEL: Kajian Feminisme Mitos Kecantikan Tokoh Perempuan Novel Induk Gajah Karya Ira Gita Sembiring sebagai Bahan Ajar Materi Teks Novel Tingkat SMA) - Desilia Putri Mediah; Suntoko; Roni Nugraha Syafroni (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This study focuses on the aspect of the form of the beauty myth in the novel Induk Gajah by Ira Gita Sembiring (2023). The analysis was carried out by utilizing Naomi Wolf's feminist theory. The formulation of the problem in this study is: (1) the aspect of intrinsic elements in the novel; (2) the form and influence of the beauty myth in the novel; and (3) recommendations for the results of the discussion as teaching materials for high school level novel texts. This research is a literature study with a qualitative descriptive approach. Data were obtained through reading and note- taking techniques. Analysis techniques include data reduction, data presentation, and drawing conclusions. The plot in the novel Induk Gajah by Ira Gita Sembiring is a mixed plot. The female character in the novel is named Ira Gita Sembiring, a fat woman who is 30 years old. The depiction of the setting in the novel includes many places with certain times and conditions. 3 forms of beauty myths were found in the novel, namely: (1) beauty as a male institution, (2) beauty as an exchange system, and (3) beauty objectively and universally. The efforts made by female characters to fight the myth of beauty are by cultivating personal admiration, self-confidence, and ultimately achieving a sense of self-acceptance. The recommendation as a teaching material for novel texts at the high school level in the form of an e-module that will be used for the learning process in the field of Indonesian language in schools.